1996
DOI: 10.1007/bf00053791
|View full text |Cite
|
Sign up to set email alerts
|

Natural and anthropogenic C2 to C6 hydrocarbons in the central-eastern Venezuelan atmosphere during the rainy season

Abstract: The levels of low molecular weight hydrocarbons were measured at pristine sites and rural locations affected by hydrocarbon emissions from oil and gas producing fields in Venezuela. At the clean sites, lower concentrations of C2 to C6 alkanes were observed, whereas, in comparison with remotes sites, very much higher levels were measured at the polluted sites. Alkenes present relatively high concentrations, with isoprene being the most abundant, all over the study region. The main sources of alkenes are likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
(41 reference statements)
2
11
0
Order By: Relevance
“…Surprisingly, the three data sets show quite different details, not only in the levels of isoprene, but also in the shape of the diurnal variations. The isoprene variation recorded at Calabozo during the wet season, is very similar to the one found at the same site during an earlier measurement campaign (13–23 September 1993), when samples were collected in canisters and the analysis was made by gas chromatography [ Donoso et al , 1996]. During the wet season, maximum mixing ratios of about 3.1 nmol/mol were recorded between 1200 and 1500 local time.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Surprisingly, the three data sets show quite different details, not only in the levels of isoprene, but also in the shape of the diurnal variations. The isoprene variation recorded at Calabozo during the wet season, is very similar to the one found at the same site during an earlier measurement campaign (13–23 September 1993), when samples were collected in canisters and the analysis was made by gas chromatography [ Donoso et al , 1996]. During the wet season, maximum mixing ratios of about 3.1 nmol/mol were recorded between 1200 and 1500 local time.…”
Section: Resultssupporting
confidence: 80%
“…Recently, Karl et al [2001] measured at the high mountain Sonnblick Observatory, Austria, high concentrations of 1‐penten‐3‐ol coming from freeze damaged leaves, which also is detected at mass 69. We do not believe that other compounds than isoprene contributed to the signal at mass 69 in Venezuela owing to following facts: We did not measure high concentrations of other leave‐wounding compounds; freeze damages do not occur; and even slightly higher levels of isoprene had been measured using the GC‐technique at the same site in an earlier campaign [ Donoso et al , 1996]. During the dry season campaign in Calabozo, however, there was some influence from biomass burning and thereby some contribution to mass 69 from other compounds than isoprene.…”
Section: Measurement Techniquesmentioning
confidence: 99%
“…In the Amazon basin the model predicts ∼1.3 nmol/mol C 2 H 4 and 0.2 nmol/mol C 3 H 6 , in agreement with the observations [ Greenberg and Zimmerman , 1984; Zimmerman et al , 1988]. Comparison with measurements in Venezuela [ Donoso et al , 1996] does not give a clear picture for C 2 H 4 , but propene observations are mostly underestimated.…”
Section: Nonmethane Hydrocarbonssupporting
confidence: 76%
“…Although butane in the atmosphere comes predominantly from anthropogenic sources (Kesselmeier and Staudt, 1999), some studies have reported emission of n-butane from vegetation (Donoso et al, 1996;Greenberg and Zimmerman, 1984;Hellén et al, 2006;König et al, 1995;Zimmerman et al, 1988). The MEK yield from n-butane oxidation is ∼ 80 % (Singh et al, 2004).…”
Section: Introductionmentioning
confidence: 99%